Structural parameter dependence of directed current generation in GaAs nanowire-based electron Brownian ratchet devices. (15th April 2015) - Abe, Yushi; Kuroda, Ryota; Ying, Xiang; Sato, Masaki; Tanaka, Takayuki; Kasai, Seiya
Abstract: We investigated the structural parameter dependence of the directed current in GaAs-nanowire-based Brownian ratchet devices. The directed current was generated by flashing a ratchet potential array repeatedly using multiple asymmetric gates with a periodic signal. The amount of current in the fabricated device increased as the nanowire width W decreased, which contradicted the theoretical model. The current also depended on the number of the gates N, when N was smaller than 6. We discussed the obtained results in terms of the structural parameter dependence of carrier transfer efficiency and the effect of electron reservoirs on current generation in flashing ratchet operation.